Novel Putative Tymoviridae-like Virus Isolated from Culex Mosquitoes in Colombia (2023)
ABSTRACT: The family Tymoviridae comprises positive-sense RNA viruses, which mainly infect plants. Recently, a few Tymoviridae-like viruses have been found in mosquitoes, which feed on vertebrate sources. We describe a novel Tymoviridae-like virus, putatively named, Guachaca virus (GUAV), isolated from Culex pipiens and Culex quinquefasciatus species of mosquitoes and collected in the rural area of Santa Marta, Colombia. After a cytopathic effect was observed in C6/36 cells, RNA was extracted and processed through the NetoVIR next-generation sequencing protocol, and data were analyzed through the VirMAP pipeline. Molecular and phenotypic characterization of the GUAV was achieved using a 5'/3' RACE, transmission electron microscopy, amplification in vertebrate cells, and phylogenetic analysis. A cytopathic effect was observed in C6/36 cells three days post-infection. The GUAV genome was successfully assembled, and its polyadenylated 3' end was corroborated. GUAV shared only 54.9% amino acid identity with its closest relative, Ek Balam virus, and was grouped with the latter and other unclassified insect-associated tymoviruses in a phylogenetic analysis. GUAV is a new member of a family previously described as comprising plant-infecting viruses, which seem to infect and replicate in mosquitoes. The sugar- and blood-feeding behavior of the Culex spp., implies a sustained contact with plants and vertebrates and justifies further studies to unravel the ecological scenario for transmission.